The Contribution of Learning Motivation to Student Learning Outcomes in Cultural Arts Subjects - Purmasari, Inka; Marzam (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to determine the effect of learning motivation on learning outcomes in cultural arts subjects of class X students of SMA N 3 Payakumbuh. This type of research is quantitative research. the population is all students of class X SMA N 3 Payakumbuh. The population is all class X students of SMA N 3 Payakumbuh, totalling 401 with a sample of 80 people. Data collection techniques in this study were questionnaires, documentation, observation and interviews. The data analysis technique was carried out by simple regression analysis using SPSS version 22 for windows. The results showed that there was a significant influence between learning motivation on the learning outcomes of class X students of SMA N 3 Payakumbuh, the rest with was the influence of other variables that were not included in the study. Average (Mean) learning motivation variables of class X SMA N 3 Payakumbuh students in the high category. Average (Mean) variable learning outcomes of class X SMA N 3 Payakumbuh students in the medium category.